2023
DOI: 10.1186/s12912-023-01256-2
|View full text |Cite
|
Sign up to set email alerts
|

Generational effect on nurses’ work values, engagement, and satisfaction in an acute hospital

Abstract: Background The present nursing workforce comprises four generational of nurses working side–by–side. While such a generation blend adds invaluable diversity to the workforce, it also brings added complexity. The study aimed to describe and summarise work values and attitudes of four nursing generations, namely Baby boomers, Generation X, Y and Z. Method A cross-sectional questionnaire study was adopted. A total of 778 nurses from an acute hospital … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Recent studies further exemplify this inconsistency. For example, in the realm of work values research, Kalleberg and Marsden (2019) offer contrasting findings compared to Rani and Samuel (2016) and Tan and Chin (2023), who observed generational differences. Similarly, Tan and Chin (2023) identified generational distinctions when examining workplace attitudes, whereas Cucina et al (2018) reported conflicting results.…”
Section: Generational Differencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies further exemplify this inconsistency. For example, in the realm of work values research, Kalleberg and Marsden (2019) offer contrasting findings compared to Rani and Samuel (2016) and Tan and Chin (2023), who observed generational differences. Similarly, Tan and Chin (2023) identified generational distinctions when examining workplace attitudes, whereas Cucina et al (2018) reported conflicting results.…”
Section: Generational Differencesmentioning
confidence: 98%
“…In contrast, Kowske et al (2010) challenged this notion, arguing that the perceived generational differences do not justify the substantial costs of tailoring interventions for each generation. To date, this research continues to be a topic of interest, exemplified by the recent study conducted by Tan and Chin (2023).…”
Section: Intergenerational Conflict Managementmentioning
confidence: 99%
“…For the first time in recent history, most of the nursing workforce at the bedside are newly graduated nurses. 13 Although the Just Culture model is an accepted model of responding to errors in many healthcare organizations, it is not yet accepted in nursing education. Most nursing education programs have policies and guidelines that align more with a punitive culture, 8 not one of Just Culture despite the position statements from the ANA and the National League for Nursing calling for the application of Just Culture in academic settings.…”
Section: Promoting a "Just Culture" For Nursing Studentsmentioning
confidence: 99%
“…A noticeable generational shift is evident in health care systems, both in Europe and abroad, characterized by the increasingly common employment of younger individuals. These younger future health care employees bring a higher proficiency in technology and information literacy [10,11], attributes cultivated from growing up in an era dominated by modern technology [12]. Technology-enhanced learning (TEL) approaches, developed to improve adult BLS knowledge and skill retention, ultimately aim to increase out-of-hospital cardiac arrest (OHCA) survival [8].…”
Section: Introductionmentioning
confidence: 99%